Examining the Influence of Economic Factors on the Competitive Advantage of Consumer Goods Manufacturing Companies in Nigeria - Adedoyin Opeyemi Okusanya; Taiwo O. Keinde; Victor E. Essang; Temitope A. Olusola (Universitas Pendidikan Ganesha, 2025)
The research problem discussed in this study relates to how economic factors affect the competitive advantage of consumer goods manufacturing companies in Nigeria. In recent years, Nigeria's economic conditions have experienced significant fluctuations due to various dynamics, including inflation, unstable exchange rates, trade policies, and varying interest rates. The purpose of this study is to analyze and understand the extent to which economic factors affect the competitive advantage of consumer goods manufacturing companies in Nigeria. The data analysis method used in this study is quantitative analysis with an inferential statistical approach. This type of research is qualitative research. The data analysis method uses quantitative analysis with an inferential statistical approach. This study adopted a cross-sectional survey research design. A sample size of 568 was used. Primary data was collected through a questionnaire. The results of the study show that economic factors have a statistically significant influence on the competitive advantage of several selected consumer goods companies in Nigeria. The implications of this study can be a reference for academics and other researchers in developing theories or strategic models that are relevant to the economic dynamics in the region.